(untitled) (International Journal of Medical and Surgical Sciences, 2016)
Early neonatal sepsis is proven infection that occurs in the newborn before 72 hours of life. The objective of the study was to determine the epidemiological and clinical characteristics of newborns with early sepsis in the Santa Barbara Integrated Hospital during January 2014 to December 2015. Quantitative, descriptive, transversal study in neonatology room of the Hospital. The universe; 1146 and the sample 136 obtained by probabilistic systematic random sampling. Data collection was through expert judgment validated questionnaire. Analysis with SPSS, version 19. The prevalence of early neonatal sepsis was 60.6 %, maternal age ranged from 15-43 years, with 21 fashion and ave- rage 25. 7 years, 92 % (125) came from rural areas, 40.4 % (55) were illiterate, 36.8 % (50) were primiparous. 59 % (80) 5 or more prenatal visits, of which 89 (65.4 %) were performed in a Health Center, doctor performed. 44.0 % (30) had urinary tract infection without treatment before delivery. 53.7 % (73) of infants were male, 26.5 % (36) had fever in the first few hours of life, it was found that 22 (16.2 %) of the infants had complications. Condition at time of exit was; Medical release 127 (93.4 %), 9 (6.6 %) were referred to hospital more complex and none died. The prevalence of early neonatal sepsis in the hospital is high, most often in children of primiparous mothers, illiterate, with urinary tract infections and untreated vaginosis and male infants.